Disaster response and emergency risk management in Ethiopia - Graham, John; Rashid, Shahidur; Malek, Mehrab (University of Pennsylvania Press, 2012)
Agrarian communities dependent on rainfall are vulnerable to production shortfalls due to drought and other climatic shocks. The human suffering caused by such shocks is often amplified due to deficiencies in market fundamentals, such as roads, information, and risk management institutions. This has been the case in Ethiopia for several centuries, dating back to medieval chronicles of the ninth century (Pankhurst 1985; von Braun, Teklu, and Webb 1998), when droughts caused widespread food insecurities and, in extreme cases, famine.